Penerapan metode HOT-Fit untuk mengevaluasi tingkat keberhasilan sistem informasi Healthical di Kota Palembang - Anggitta Ratu; Sri Andayani (AITI, 2026)
Healthical is a healthcare management information system implemented in 2024 across all public health centers in Palembang to improve the effectiveness and efficiency of healthcare services. The system was designed to support the recording, reporting, and integrated management of services and healthcare administration processes. However, several challenges have emerged during its implementation, including server disruptions, limited integration, limited features, and suboptimal security. Therefore, this study aims to evaluate Healthical’s implementation using the Human, Organization, and Technology-Fit (HOT-Fit) model, which comprises eight research variables. This study used a quantitative approach, involving 115 system users selected through saturated sampling. The data were analyzed with PLS-SEM using SmartPLS 4.0. Three of ten hypotheses were rejected: system quality and service quality on user satisfaction, and system use on net benefits. Based on these findings, several recommendations are proposed, including improving system features and data security, strengthening system integration, providing user training, improving technological infrastructure, and conducting regular evaluations to optimize the implementation of Healthical.